The family of woman : lesbian mothers, their children, and the undoing of gender - Sullivan, Maureen, 1963- (Berkeley : University of California Press, 2004)
Amidst the shrill and discordant notes struck in debates over the make-up - or breakdown - of the American family, the family keeps evolving. This book offers a close and clear-eyed look into a form this change has taken most recently, the lesbian coparent family. Based on intensive interviews and extensive firsthand observation, The Family of Woman chronicles the experience of thirty-four families headed by lesbian mothers whose children were conceived by means of donor insemination. With its intimate perspective on the interior dynamics of these families and its penetrating view of their pub.
The emergence of lesbian-coparent families in postmodern society -- Becoming parents : baby making in the age of assisted procreation -- Being parents : the end of Oedipus and the expansion of intimacy -- Undoing the gender division of labor -- Truth and reconciliation : families of origin come around and come out -- Becoming familiar in the community of strangers -- The structure of donor-extended kinship -- The theoretical future of a conscious feminist kinship -- Appendix: Families by the bay : the study design, method, and participants.
Includes bibliographical references (pages 285-303) and index.
Print version record.
JSTOR
Keywords: Lesbian mothers -- United States -- Case studies; Children of gay parents -- United States -- Case studies; Sex role -- United States -- Case studies; Mères lesbiennes -- États-Unis -- Études de cas; Enfants de parents homosexuels -- États-Unis -- Études de cas; Rôle selon le sexe -- États-Unis -- Études de cas; FAMILY & RELATIONSHIPS -- Parenting -- Motherhood; SOCIAL SCIENCE -- Gender Studies; Children of gay parents; Lesbian mothers; Sex role; United States; Case studies